Love, the Cosmos and the Raging Sea: The Surrealist Ecopoetics of César Moro (2024)
In César Moro’s poetry, we can identify a consistent endeavor towards cosmic communion and the revival of the mythical vision that typified the rituals and relationships with nature of the ancient Amerindian cultures of Peru. This article elucidates these tendencies in the oeuvre of the Peruvian surrealist poet, specifically through the analysis of selected prose poems. These poems are primarily from the collection titled Cartas (1939), and ‘Biografía peruana’, a part of the book Los anteojos de azufre (1958). The personal appropriation of the surrealist proposition carried out by Moro, along with its mythical, imaginative, and emotional connections to the Andean territories, will be highlighted. The ecopoetic and hermeneutics approach of Moro’s work exhibit the possibilities and limits of the avant-garde and modern proposals to link the human being with the cosmic totality